Perceptions on the Use of the Flipped Classroom in the EFL Class - Nadia Lilian Lagunes-Reyes; María de los Milagros Cruz-Ramos; Mario Alberto Sandoval-Sánchez (Asociación Colombiana de Profesores de Ingles, 2022)
The present action-research study analyzes students' basic perceptions about the use of the Flipped Classroom as part of their EFL class in a Mexican technical high school. To this end, 47 5th-semester students took two versions of a survey, which combined provided an understanding of their views after having taken part of a six-week intervention. The intervention focused on what is typically considered the most challenging topic of the semester: the simple past and its functions included in the official syllabus. On the one hand, the 'flipped' part of the lessons was divided into before and after-class online activities following a set of principles for the Flipped Classroom, Communicative Language Teaching, and Multimedia Instruction. On the other hand, in-class activities focused on reviewing content and communicative oral practice. The Flipped Classroom was favorably regarded. Students perceived it as a technique to facilitate a rapid improvement of certain aspects of speaking performance, especially in regards to fluency, comprehension, and vocabulary.